SISTEM PENAWARAN DAN PENJADWALAN MATA KULIAH DENGAN METODE K-MEDOIDS DAN PENDEKATAN ALTERNATIF GRAPH COLORING - Mishelle Tirtajaya Winartha; Lely Hiryanto (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Class offers and scheduling application is made by using k-medoids and alternative graph coloring approach. This application optimizes the offers of class scheduling. The sample case is Faculty of Information Technology at Tarumanagara University. k-Medoids is used to acquire the number of classes that need to be offered on new semester and alternative graph coloring approach is used to acquire the class that has been adjusted with lecturer’s time and room availability. The results still indicate the violation of soft constraint. The most frequent violation of soft constraint is the mismatch schedule to lecturer’s time availability. Key wordsAlternative Graph Coloring Approach, Fakultas Teknologi Informasi Universitas Tarumanagara, k-Medoids, University Course Timetabling Problem